Trophic niche differentiation in rodents and marsupials revealed by stable isotopes - Galetti, Mauro [UNESP]; Rodarte, Raisa Reis [UNESP]; Neves, Carolina Lima [UNESP]; Moreira, Marcelo; Costa-Pereira, Raul [UNESP] (Public Library of Science (PLoS), 2016)
Tropical rainforests support the greatest diversity of small mammals in the world, yet we have little understanding about the mechanisms that promote the coexistence of species. Diet partitioning can favor coexistence by lessening competition, and interspecific differences in body size and habitat use are usually proposed to be associated with trophic divergence. However, the use of classic dietary methods (e.g. stomach contents) is challenging in small mammals, particularly in community-level studies, thus we used stable isotopes (δ13C and δ15N) to infer about trophic niche. We investigated i) how trophic niche is partitioned among rodent and marsupial species in three Atlantic forest sites and ii) if interspecific body size and locomotor habit inequalities can constitute mechanisms underlying the isotopic niche partitioning. We found that rodents occupied a broad isotopic niche space with species distributed in different trophic levels and relying on diverse basal carbon sources (C3 and C4 plants). Surprisingly, on the other hand, marsupials showed a narrow isotopic niche, both in δ13C and δ15N dimensions, which is partially overlapped with rodents, contradicting their description as omnivores and generalists proposed classic dietary studies. Although body mass differences did not explained the divergence in isotopic values among species, groups of species with different locomotor habit presented clear differences in the position of the isotopic niche space, indicating that the use of different forest strata can favor trophic niche partitioning in small mammals communities. We suggest that anthropogenic impacts, such as habitat modification (logging, harvesting), can simplify the vertical structure of ecosystems and collapse the diversity of basal resources, which might affect negatively small mammals communities in Atlantic forests.